(3MjGI GdMjhGfs - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s ((3eMeO Hf eMeO Hf jhSa GdTGaYi GdefRdi s)
(3ChdgG (B:s
(3jHOC GdehLhO efg CKfGA HGH GdNGA HGdMOjK Yf GdNdb Hbhdg (B: (3hLO NddkG aONd ajg MJi bdY GdSO haGV Ydi CehGdge s
(3BNQgG (B:s
(3jfJgi HHGH GdjGA hGHJOF Hedc GdhMT GdPi efg GdTLGeYI JbJVi hMSHfG Gddg JYGdi hcai s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fbdJ ef fSNI cJHJ ef fSNI GdeDda hHgG SbW bHjd BNQgG ai GdhQbI (B211(3H CKfGA HGH GdjGA s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs